Case Report: MIS-C Temporarily Associated With COVID-19 Complicated by Reye's Syndrome - Pessoa, Fabrício Silva; Lacerda, Eliza Maria da Costa Brito; Gonçalves, Valdênia Costa; Tanaka, Barbara Neiva (Frontiers in Pediatrics, 2021)
We describe a 7-year-old child with multisystemic inflammatory syndrome that was temporarily associated with the novel coronavirus disease which evolved into serious illness, with coronary aneurysm, using human immunoglobulin and acetylsalicylic acid, in which clinical manifestations including hepatitis, convulsions, and coma were aggravated with Reye's syndrome. To date, there has been no report of the association of multisystemic inflammatory syndrome that is temporarily associated with the novel coronavirus disease and Reye's syndrome.